2020
DOI: 10.1177/0890117120929131
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Wellness Champions on the Effectiveness of a Workplace Health and Well-Being Program

Abstract: Purpose: To evaluate the impact of Desire2Move (D2M) implementation fidelity by Wellness Champions on program effectiveness. Design: Cross-sectional. Setting: Years 1, 3, and 5 of D2M; an annual peer support health and well-being initiative for university employees. Participants: D2M participants included 422 employees from 28 teams; however, only 144 provided survey data (34.1% response rate). Intervention: During the 8-week program, departments competed as teams to accumulate the greatest average physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Similarly, given that BE@Work was facilitated by a researcher experienced in the delivery of groupbased exercise, the intervention may have been subject to intervention delivery agent bias. Future work could seek to train employees to deliver HIIT sessions, such as workplace wellness champions involved in previous workplace health promotion interventions (Ellis et al, 2021). Furthermore, participants in this study were healthy middle-aged adults working in officebased roles; therefore the findings cannot be extended to more diverse populations or workplaces.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, given that BE@Work was facilitated by a researcher experienced in the delivery of groupbased exercise, the intervention may have been subject to intervention delivery agent bias. Future work could seek to train employees to deliver HIIT sessions, such as workplace wellness champions involved in previous workplace health promotion interventions (Ellis et al, 2021). Furthermore, participants in this study were healthy middle-aged adults working in officebased roles; therefore the findings cannot be extended to more diverse populations or workplaces.…”
Section: Limitationsmentioning
confidence: 99%
“…Moreover, there was a facilitative effect whereby managers advocated and actively recruited participants for the intervention. Although there was an element that being a PC was perceived as part of the work role [36] . Nudges are a popular strategy to help people make changes to their behaviours and our findings support the contention that they can be employed in workplaces [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Participants then followed the same routine as those who voluntarily decided to stand and move. To support the behaviour change process, the design incorporated work managers across sections of the organisation to act as voluntary PC to model the new health behaviour during work [36] . PC completed a two-hour training session with a curriculum content of; education about the health concerns associated with prolonged sitting and sedentary behaviour, the design of the intervention, use of the software and time for PC to ask clarifying questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shapiro–Wilk and Levene’s tests were used to verify data normality and the homogeneity of variances at each time point. Trait EI data were analyzed: (a) using correlational analysis with recovery stress states scores on the total sample; and (b) by dividing its scores into either a high or low group based on the median value, a common practice within the literature [ 46 , 47 , 48 ]. While dichotomization is sometimes criticized in the literature [ 49 ], recent re-evaluations have shown that this practice is a robust, reliable, and appropriate statistical analysis when independent variables are uncorrelated [ 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%